Exploring the multifaceted role of creativity in an elite football context - Torp Rasmussen, L. J.; Glaveanu, V. P.; Østergaard, L. D. (Qualitative Research in Sport, Exercise and Health, 2020)
In recent years, creativity in team ball sports has been portrayed from several theoretical perspectives. Despite the growing research in the area, there is a lack of studies on practitioners` understanding of creativity. Growing out of and informing practices in continuous cycles, coaches` conceptions are shaped by transactions between social and cultural processes and the coaches` personal interests and desires. Therefore, coaches acquire unique and changeable sets of conceptions. Hence, the purpose of this study was to explore, analyse and contrast qualitatively different conceptions of creativity in football. Specifically, we mapped the different ways in which coaches from the Danish club Aalborg BK conceived of creativity, its importance in football, and its application in practice. The main data production comprised 18 semi-structured interviews, and, among other methods, participant observation of day-to-day practices at four elite youth teams was applied to ground interpretations in contextual knowledge. Phenomenographic analysis led to 15 metaphors, which capture varied meanings, benefits and applications of creativity in football, i.e. surgicality, productivity, navigation, choreography, circus, design, survival, deception, independence, co-creation, style, exploration, transgression, magic and invention. These results may stimulate more nuanced dialogues about creativity. Contrasting the coaching interests served by the metaphors, we show how diverse conceptions emerged and operated to 1) enable solving of in-game problems, 2) stimulate engagement, 3) facilitate learning, or 4) enhance the chance to win matches. These orientations involve diverse ways to apply creativity. While some bearings entail promising potentials for development settings, others may have limiting consequences for players experiences.